Genetic Diversity of Bovine Pestiviruses Detected in Backyard Cattle Farms Between 2014 and 2019 in Henan Province, China - Shi, Hongfei; Li, Huan; Zhang, Yang; Yang, Lulu; Hu, Yun; Wang, Zhicheng; Duan, Lisha; Leng, Chaoliang; Yan, Baolong; Yao, Lunguang (Frontiers in Veterinary Science, 2020)
Bovine pestiviruses include Pestivirus A (BVDV-1), Pestivirus B (BVDV-2), and Pestivirus H, which was originally called HoBi-like pestivirus. We conducted an epidemiological investigation for pestiviruses circulating in backyard cattle farms in central China. RT-PCR assays and sequences analysis were conducted on 54 nasal swabs, 26 serum samples, and three lung samples from cattle with respiratory infections and identified 29 pestivirus strains, including 24 Pestivirus A and five Pestivirus H strains. Phylogenetic analysis based on partial 5’-UTR and Npro sequences showed that the genotypes of 24 Pestivirus A strains included Pestivirus A 1b (6 isolates), Pestivirus A 1m (6 isolates), Pestivirus A 1q (2 isolates), Pestivirus A 1u (1 isolates), and Pestivirus A 1o (9 isolates, a putative new sub-genotype). In addition, a single “Pestivirus H a” genotype included all five Pestivirus H strains. This study revealed extensive genetic variations within bovine pestivirus isolates derived from cattle in backyard farms in Central China, and this epidemiological information improves our understanding of the epidemics of bovine Pestiviruses, as well as will be useful in designing and evaluating diagnostic methods and developing more effective vaccines.